2019
DOI: 10.3390/ma12162537
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Carbon Nanospheres in Photocatalyst Production: From Composites to Highly Active Hollow Structures

Abstract: Titanium dioxide–carbon sphere (TiO2–CS) composites were constructed via using prefabricated carbon spheres as templates. By the removal of template from the TiO2–CS, TiO2 hollow structures (HS) were synthesized. The CS templates were prepared by the hydrothermal treatment of ordinary table sugar (sucrose). TiO2–HSs were obtained by removing CSs with calcination. Our own sensitized TiO2 was used for coating the CSs. The structure of the CSs, TiO2–CS composites, and TiO2–HSs were characterized by scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In our previous publication, we demonstrated that not only the synthesis conditions of TiO2 coating but also that the parameters applied during the preparation of CSs can significantly affect the properties of the resulting titania [21]. In this paper, we present the importance of the purification solvent by using either acetone or ethanol to eliminate the residual organic contaminants formed during the synthesis of CSs, since it was observed that this parameter might be the most crucial of all in our system.…”
Section: Textural Characterizationmentioning
confidence: 87%
“…In our previous publication, we demonstrated that not only the synthesis conditions of TiO2 coating but also that the parameters applied during the preparation of CSs can significantly affect the properties of the resulting titania [21]. In this paper, we present the importance of the purification solvent by using either acetone or ethanol to eliminate the residual organic contaminants formed during the synthesis of CSs, since it was observed that this parameter might be the most crucial of all in our system.…”
Section: Textural Characterizationmentioning
confidence: 87%
“…Carbon spheres have been widely researched and applied to various fields-including batteries, photocatalysis, capacitors, and fuel cells-due to their easily available sources and facile synthesis. The last few decades have witnessed a rapid growth in sustainable energy field and this has led to the research of various application and approaches of carbon spheres, including carbonization routes [29], chemical vapor deposition (CVD) [30], ultrasonic-spray [31], and hydrothermal carbonization (HTC) [6,32,33]. Among these methods, hydrothermal carbonization is the one that aroused the greatest interest due to its facile procedure and mild experimental condition.…”
Section: Carbon Sphere Template-overview Of Synthesismentioning
confidence: 99%
“…This is the critical superiority when carbon spheres are applied as templates. Moreover, many researchers are focusing on a wide range of source to obtain carbon spheres by hydrothermal reaction, including general monosaccharide (xylose [38], glucose [38]), disaccharides (sucrose [6,38], lactose [39]), polysaccharides (starch [40,41], cellulose [42]), and some biomasses [39]. The possible formation procedure is shown schematically in Figure 2.…”
Section: Carbon Sphere Template-overview Of Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…not crystalline) carbon was used [220][221][222]. Conversely, the hollow spherical morphology can enhance the photocatalytic activity via enhancing the light trapping properties of the photocatalyst [21,73,99,146,155,160,161].…”
Section: Morphological Modification [73 99]mentioning
confidence: 99%